Utilization CSRS-PPP software for recovery aircraft’s position - Kamil KRASUSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The PPP method is applied in aeronautical navigation as a new technique for determination of aircraft’s position. In this paper preliminary results of recovery aircraft’s position were presented. The raw GPS observations from Topcon dual-frequency receiver were utilized to position obtained with temporal resolution 1 second. Service on-line CSRS-PPP was used for estimation vehicle coordinates and receiver clock, troposphere delay and ambiguity term also. Preliminary results of aircraft’s position show that accuracy of horizontal coordinates is about 3 cm and less than 7 cm for vertical coordinate, respectively. The high level accuracy of coordinates is assured by using precise products such as GPS ephemeris and clocks.